2022
DOI: 10.3389/fpubh.2022.968231
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to hand hygiene compliance in intensive care units during the COVID-19 pandemic: A qualitative study

Abstract: BackgroundThe practice of hand washing is an effective way to prevent contamination and disease transmission. Following the COVID-19 pandemic, hand washing has become increasingly important. Therefore, this qualitative study aimed to understand barriers to hand hygiene compliance among healthcare workers during the COVID-19 pandemic.Materials and methodsTwenty-five healthcare workers from intensive care units were sampled using purposive sampling in a qualitative content analysis study. Data were collected thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…Regarding barriers to Covid-19 vaccine and handwashing uptake, previous research ndings agree with study ndings. A study to investigate hand hygiene barriers in a teaching hospital's intensive care unit in southeast Iran (12), found out that a lack of quality equipment reduced hand hygiene practices. The study revealed poor quality soap resulting in skin dryness and itching, and a shortage of disinfectants led to minimal hand hygiene compliance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding barriers to Covid-19 vaccine and handwashing uptake, previous research ndings agree with study ndings. A study to investigate hand hygiene barriers in a teaching hospital's intensive care unit in southeast Iran (12), found out that a lack of quality equipment reduced hand hygiene practices. The study revealed poor quality soap resulting in skin dryness and itching, and a shortage of disinfectants led to minimal hand hygiene compliance.…”
Section: Discussionmentioning
confidence: 99%
“…The Coronavirus disease 2019 has brought about unprecedented challenges globally, threatening to undo the decades of progress on poverty, health systems and education (1). To date, the pandemic has resulted to more than 6.7 million deaths worldwide, loss of jobs equivalent to 114 million globally and about half of the world's 3.3 billion workforce is at the verge of losing their livelihoods 12 , thus raising many concerns in everyone's, mind especially about how to respond to the pandemic (1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Master of the correct hand washing method (7-step washing technique) and timing. [54][55][56][57] Step 1 (inside): wash your hands, wet your hands with running water, apply hand sanitizer, keep your palms opposite, and rub your fingers together; Step 2 (outside): wash the back finger seam, rub the palm of your hand and the back of your hand along the finger seam, and exchange your hands; Step 3 (clip): wash the palm side finger seam, the palms are opposite, and the hands cross and rub each other along the finger seam; The fourth step is to bend the fingers on the back and rub the fingers on the other hand; Step 5 (big): wash the thumb, hold the thumb of the other hand in one hand, rotate and rub it, and exchange hands; Step 6 (standing): wash the fingertips, bend the finger joints, close the fingertips to the palm of the other hand, rotate and rub, and exchange hands; Step 7 (wrists): wash wrists and arms, rub wrists and arms, and exchange hands. The rubbing time for each step of the hand washing should be greater than 15 seconds.…”
Section: 12 Hand Hygienementioning
confidence: 99%
“…Being around highcompliance co-workers (i.e., role models) is a typical example of a positive and valuable social influence (Hoffmann et al, 2020). In Ahmadipour et al (2022), HCWs reported the existence of negative models, such as the influence of experienced nurses or physicians who did not adhere to HH guidelines, as a reason for their noncompliance. Self-efficacy refers to an individual's belief in their ability to succeed in a given situation.…”
Section: Introductionmentioning
confidence: 99%